(untitled) - Solbrig, Otto T. (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Las caprifoliaceas silvestres y cultivadas en la Argentina (1961)

(untitled)
The Caprifoliaceae found in Argentina are studied taxonomically with notes on distribution, horticulture and uses. Descriptions and keys for the determination of genera and species are given. All together 7 genera and 28 species are found in Argentina: 3 species (Sambucus autralis, S. peruviana and Viburnum seemenii) grow wild, one species (Lonicera japonica) is naturalized, while the rest grow only under cultivation, some being found very infrequently.